Analisa Pengaruh Modifikasi Pemasangan Solenoid Valve Pada Mesin Chiller Di Kantor BKN Pusat - Rulan Fazriawan; Delvis Agusman (Prosiding Seminar Nasional Teknoka, 2024)
The air conditioning machine used at Head office BKN is air-cooled chiller machine. This chiller machine works by utilizing a vapor compression cycle. The four main components in the vapor compression cycle are: compressor, condenser, expansion valve and evaporator. The vapor compression cycle will run repeatedly as long as the chiller machine is activated. The problem with this cycle is that when the chiller machine is deactivated, the liquid refrigerant (R134A) will return to the compressor, which can cause leaks/clogging. To keep the chiller in normal condition, a solenoid valve is installed between the evaporator flow and the compressor. A solenoid valve is an electromagnetic valve that functions to control the flow of air or water. In this research, tests were carried out on chiller machines that had solenoid valves installed and those that had not been installed. The results of the research are that chiller machine compressors that have solenoid valves installed have a more stable temperature. Life time of a compressor with a stable temperature is longer